Pengaruh Green Accounting, Profitabilitas dan Corporate Social Responsibility terhadap Sustainable Development Goals dengan Ukuran Perusahaan sebagai Variabel Moderasi: Studi pada Perusahaan Manufaktur yang Terdaftar di BEI - Adnyana, I Wayan Putra; Adiputra, I Made Pradana; Musmini, Lucy Sri (Ekuitas: Jurnal Pendidikan Ekonomi, 2024)
Attention to environmental issues caused by company activities, especially in the manufacturing sector, is very important. Although many companies implement green accounting, profitability, and corporate social responsibility (CSR), the main challenge lies in measuring their impact on sustainable development goals (SDGs). This study aims to examine the effect of green accounting, profitability, and CSR on SDGs with firm size as a moderating variable. The sample consisted of 25 manufacturing companies listed on the IDX during the 2020-2023 period selected using a purposive sampling technique resulting in 100 observations. Data were collected using a documentation approach sourced from annual reports, sustainability reports, and PROPER reports and analyzed using the PLS-SEM method. Hypothesis testing was carried out using patch analysis. The results of the study indicate that (1) green accounting has a positive and significant effect on SDGs (p-values ​​0.000), (2) profitability does not have an effect on SDGs (p-values ​​0.225), (3) CSR has a positive and significant effect on SDGs (p-values ​​0.001), (4) firm size weakens the effect of green accounting on SDGs (p-values ​​0.000 and original sample -0.265), (5) firm size cannot moderate the effect of profitability on SDGs (p-values ​​0.381), and (6) firm size cannot moderate the effect of CSR on SDGs (p-values ​​0.599). This study contributes to the development of legitimacy theory and stakeholder theory and provides practical implications for companies in managing social and environmental impacts more effectively.